Agrigent, Italien: Das Olympieion - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2023)
The Temple of Olympian Zeus (or Olympeion) in Agrigento, Sicily was the largest Doric temple ever constructed, although it was never completed and now lies in ruins. It stands in the Valle dei Templi with a number of other major Greek temples. The Greek historian Polybius mentions it briefly in a 2nd century BC description of Akragas, commenting that „the temple of Olympian Zeus being unfinished but second it seems to none in Greece in design and dimensions.“ According to Diodorus, it remained unfinished due to the Carthaginian conquest of the city (405 BC). The temple was eventually toppled by earthquakes and in the 18th century was quarried extensively to provide building materials for the modern towns of Agrigento and nearby Porto Empedocle. Today it survives only as a broad stone platform heaped with tumbled pillars and blocks of stone.